2021
DOI: 10.3390/jcm10215079
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Cardiac Rehabilitation in the Regional Cardiocerebrovascular Centers in Korea

Abstract: Regional Cardiocerebrovascular Centers (RCCs)—a Korean government initiative—seek to reduce medical gaps across regions, and their cardiac rehabilitation (CR) programs are expected to model post-acute care for the Korean CR program. Accordingly, this study aimed to evaluate the current status of CR programs in the RCCs. We distributed surveys on the CR condition, activity, and barriers to 12 RCCs in different provinces. The results revealed significant gaps in the annual number of acute myocardial infarction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Since 2008, the Ministry of Health and Welfare has designated 14 Regional Cardiocerebrovascular Centers nationwide and made the CR program mandatory to reduce regional variations and promote the distribution of CR. 17 Since February 2017, CR has been reimbursed by the National Health Insurance Service. In 2019, a highly qualified clinical practice guideline for CR tailored to the situation in Korea was published.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008, the Ministry of Health and Welfare has designated 14 Regional Cardiocerebrovascular Centers nationwide and made the CR program mandatory to reduce regional variations and promote the distribution of CR. 17 Since February 2017, CR has been reimbursed by the National Health Insurance Service. In 2019, a highly qualified clinical practice guideline for CR tailored to the situation in Korea was published.…”
Section: Discussionmentioning
confidence: 99%
“…Seoul National University Bundang Hospital is designated as one of the Regional Cardiocerebrovascular Centers (RCCs) in South Korea. 26 Following the RCC protocol, most of the patients with AMI are referred to the Department of Rehabilitation for CR. Among the patients who were admitted to Seoul National University Bundang Hospital for the treatment of AMI between August 2015 and March 2019, 1545 hospitalized patients were referred for CR.…”
Section: Methodsmentioning
confidence: 99%
“…Seoul National University Bundang Hospital is designated as one of the Regional Cardiocerebrovascular Centers (RCCs) in South Korea 26. Following the RCC protocol, most of the patients with AMI are referred to the Department of Rehabilitation for CR.…”
Section: Methodsmentioning
confidence: 99%
“…6 Department of Physical Medicine and Rehabilitation, Dong-A University College of Medicine, Busan, South Korea. 7 Department of Rehabilitation Medicine, Seoul National University College of Medicine, Seoul National University Bundang Hospital, Seongnam, South Korea. 8 Department of Rehabilitation Medicine, Chungbuk National University, College of Medicine, Cheongju, South Korea.…”
Section: Abbreviationsmentioning
confidence: 99%
“…A survey of the current status of CR in South Korean cardiocerebrovascular centers showed that approximately 47% of patients who received inpatient care for acute myocardial infarction underwent CR after discharge, with 36% undergoing early assessment and 17% continuing CR. However, the rates varied widely across facilities and compared with the high CR referral rate, CR participation and completion rates were relatively low, in Korea [ 7 ]. Worldwide, CR available is only half, and participation is restricted because most patients cannot be accepted even if they are provided [ 8 ].…”
Section: Introductionmentioning
confidence: 99%